Impact of Architectural Sculpture Design on Buildings: A Case Study of Kigezi Region. - Tumwekwase, Boaz (Kabale University, 2024)
The research presented the links between the different aids of art that were sculpture and architecture both in 2D and 3D. The great influence of expressionist sculpture on architecture was emphasized in the buildings of Kigezi region. Modern buildings could often look like built monuments. Sculptors distance themselves from their earlier version, the erection of a building – whether commercial, church, residential, or mosque, advance planning, and commitment over many years. The number of people involved in any communal project, from sponsors (whether states, or individuals) to designers, architects, and sculptors, was enormous. In studying architectural sculpture, the researcher was faced with originals, usually founded in context and with some closely dated inscriptions and references in written texts; although most sculptors who hold free-standing sculpture in such high regard had little to say about architectural compositions. Architectural sculpture emerges as a testament to human ingenuity in the realm of form and space, where concrete meets metal. It is not merely construction, but a dialogue between materiality and imagination, a dance of shadows and light. Sculpture stands, not just in physical dimensions, but also as a sculpture of thought, representing the architect's silent conversation with time and culture. Each line, curve, and angle was a verse in a poem of stone and steel, a narrative frozen in the permanence of structure. This was the essence of architectural sculpture a fusion of utility and beauty, where the mundane was elevated to the magnificent, and buildings breathed with the soul of art. This aimed to capture the essence of architectural sculpture, blending the functional aspects of architecture with the expressive nature of sculpture to create something that transcends both disciplines.